HUBUNGAN PENGETAHUAN DAN SIKAP ORANG TUA TERHADAP PEMBERIAN IMUNISASI BIAS DI SD BLANG ARA KABUPATEN NAGAN RAYA - Ira Mayani; Evi zahara; Isnaini Putri; Nanda Norisa; Kartinazahri Kartinazahri (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
This study aims to determine the relationship between parental knowledge and attitudes towards the administration of BIAS immunization at SD Blang Ara, Nagan Raya District.  This  research  employs  a  quantitative  design  with  a  cross-sectional approach. The sample consists of 48 parents of students in grades 1, 2, and 5 at SD Blang Ara. Data were collected and analyzed to determine the relationship between parental knowledge and attitudes towards immunization administration. The average score of parental knowledge about BIAS immunization is 2.33, indicating a fairly good level of knowledge. The average score of parental attitudes is 1.77, which shows a positive attitude, although not as strong as their knowledge. The analysis indicates a significant relationship between knowledge (p-value   =   0.000)   and   attitudes   (p-value   =   0.000)   of   parents   with   the administration of immunization in the BIAS program. This study shows that increasing parental knowledge and positive attitudes can enhance the level of immunization administration to children.  The  results  of  this  study  are  expected  to  provide  input  for Puskesmas Uteun Pulo to improve immunization service efforts. Puskesmas can design more effective educational programs for parents to increase immunization coverage in their working area.